Energy-efficient electrolytic hydrogen production assisted by coupling urea oxidation with a pH-gradient concentration cell. Issue 21 (19th January 2018) - Wang, Genxiang; Chen, Junxiang; Li, Yan; Jia, Jingchun; Cai, Pingwei; Wen, Zhenhai
Abstract : Electrolytic H2 generation can be greatly facilitated by coupling urea oxidation reaction and a pH-gradient concentration cell. Abstract : An unprecedented asymmetric-electrolyte electrolyzer is proposed using an acidic cathode for the hydrogen evolution reaction (HER) and an alkaline anode for the urea oxidation reaction (UOR), which significantly decreases the electrical energy required for electrolytic hydrogen production.